Identification of Phenotypic, Nutrition and Bioactive Compounds of Marigold (Tagetes erecta) in Bengkulu Province, Indonesia as Poultry Feed Material - Rita, Wismalinda; Mohammad Chozin; Sumardi; Dwatmadji (PT FORMOSA CENDEKIA GLOBAL, 2024)
Marigolds (Tagetes erecta) belong to the widely developed astraceae family and are easy to cultivate. Marigold flowers have a high content of nutrients and active compounds so that the potential to be used as poultry feed. This study aims to identify phenotypes, nutrients and bioactive compounds Marigold found in Bengkulu province Indonesia. The study was conducted using purposive sampling survey method by conducting non-experimental descriptive observations. The variables observed were phenotypic identification, nutrient content and bioactive compounds. There are 7 (seven) Marigold Accessions, Nutritional content, especially kaasar protein, is quite good at 8.75-14.23% with the highest content in the wrrl accession which is almost the same as WRRM and WRDP while the lowest is WRSJ. While the coarse fiber content is almost the same ranging from 9.19-12.08%. Accession WRRL has the lowest tannin and HCN content of 7.80% and 0.64%. Carotenoids were moderately high (327 mg/kg) at the accession of WRDP. The accession of WRRL has a better content of nutrients and bioactive compounds compared to other Accessions this shows that marigold can be used as an alternative to natural feed additives to increase poultry productivity